Cytoplasmic location of undermethylated messenger RNA in Novikoff cells. - Kaehler, M (1979)
Novikoff cells in culture were labeled with L-[methyl-3H]methionine and [U-14C]uridine in the presence of (a) TubHcy2, (b) AdoHcy, (c) homocysteine, (d) tubercidin, or (e) without any additions. Only in cultures labeled in the presence of TubHcy were undermethylated cap structures observed to represent a significant portion of [3H]methyl radioactivity. Novikoff cells in culture were then simultaneously labeled with L-[methyl-3H]methionine and [32P]orthophosphate in the presence or absence of TubHcy. Total cytoplasmic, polysomal and monosomal poly(A)-containing RNAs were analyzed. Both monosomal and polysomal mRNA fractions from TubHcy-treated cells contain partially methylated cap structures, suggesting that 2'-O-methylation of the nucleoside adjacent to the pyrophosphate linkage in caps is not required for transport, ribosomal binding or translation. Comparison of nuclear and cytoplasmic cap structures from normal and inhibited cultures indicate that an altered mRNA population is generated in the presence of TubHcy.